Profil Pasar Daging Ayam Potong di Pasar Angso Duo Kota Jambi - Rindes, Rifli (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
This study aims to determine the market structure  of chicken (broiler)  at the Angso Duo market in Jambi city. The object had observed in this study were  chicken   traders and transactions that occur in the    Angso  Duo Market  in  Jambi  City.   This  research  used census   and survey techniques of  direct observation, then  the data obtained in the  descriptive analysis. The result showed that the number of  retailer was 94.3%  and  wholesalers was 5.7%.  The education’s average of the trader was 65.15%  senior  high  school graduate.  The  average   chicken’s  price was  Rp18.693, with  the average daily gains ranged  from   Rp. 109.497   to Rp 22,818.   The   avergae  marketshare   of  retail  was  1.47%  to 1.54%.  The form of chicken market was oligopoly. The study concluded that the market structure of chicken ‘s market in the Angso  Duo  market was oligopoly.